Getting started in tax-smart investing - Westhem, Andrew D. (John Wiley & Sons, 2000)
Getting Started in Tax-Savvy Investing explains the new and ever-changing tax laws and shows you how to take full advantage of all the legal tax strategies available today, including business ownership and estate planning